Extractable Boron in Some Acid Soils of India: Status, Spatial Variability and Relationship with Soil Properties - and Brahma Swaroop Dwivedi, Sanjib Kumar Behera Arvind Kumar Shukla, Mahavir Singh (Journal of the Indian Society of Soil Science, 2016)
The present study was conducted to assess the status and spatial variability of boron (B) in some cultivated acid soils of India. Four hundred (one hundred from each series) surface (0-15 cm depth) soil samples were collected representing four soil series namely, Hariharapur, Debatoli, Rajpora and Neeleswaram, located in Odisha, Jharkhand, Himachal Pradesh and Kerala states of India, respectively, and were analyzed. The mean values of hot water soluble B (HWB) were 0.39 (mean between 0.02 to 2.92 mg kg-1), 0.54 (mean between 0.23 to 1.27 mg kg-1), 0.57 (mean between 0.26 to 1.24 mg kg-1) and 0.37 (mean between 0.01 to 2.14 mg kg-1) mg kg-1 for Hariharapur, Debatoli, Rajpora and Neeleswarm soil series, respectively. Hariharapur, Debatoli, Rajpora and Neeleswarm soil series had mean concentration of Mehlich 1 extractable B of 2.71 (mean between 0.72 to 5.72 mg kg-1), 1.07 (mean between 0.52 to 2.52 mg kg-1), 1.21 (mean between 0.48 to 2.56 mg kg-1) and 1.29 (mean between 0.28 to 4.44 mg kg-1) mg kg-1, respectively. The coefficient of variation varied between 25 to 139 per cent for extractable B. Hot water soluble B was positively correlated with organic carbon (OC) content in all soils except in Hariharapur series and with exchangeable magnesium (Mg) in soils of Hariharapur and Neeleswarm series. Geostatistical analysis revealed that the best fit models were J-Bessel and Hole effect for HWB with weak to strong spatial dependency in different soil series.